Object-Oriented Graphics Programming in C++ - Stevens, Roger T (Elsevier Science & Technology, 1994)
Object-Oriented Graphics Programming in C++ provides programmers with the information needed to produce realistic pictures on a PC monitor screen.The book is comprised of 20 chapters that discuss the aspects of graphics programming in C++.The book starts with a short introduction discussing the purpose of the book.